Six months of COVID-19 response in Nigeria: lessons, challenges, and way forward (Journal of Ideas in Health, 2020)
Background: The declaration of COVID-19 as a public health emergency by the World Health Organization necessitated countries across the globe to implement response and mitigation measures. We aimed to assess the Nigerian government's response following six months of detection of COVID-19 in Nigeria.Methods: A narrative review of existing literature on the topic was done. The authors' opinion as experts supporting the COVID-19 pandemic response was included. The review and opinion were summarized, covering six months of the outbreak response in Nigeria.Results: Contact tracing commenced after identifying the index case of COVID-19 in Nigeria but has been faced with challenges such as inadequate equipment and shortage of funds. School closure was implemented barely three weeks after detecting the index case, but the resumption of terminal classes has been announced recently. The Nigerian government implemented restrictions on gatherings involving up to 11 people after three weeks following the detection of the index case of COVID-19. The lack of enforcement and supervision of gatherings and public events made many individuals disregard the restriction measures. Lockdowns on religious gatherings and public events have been recently eased nationwide, and regulatory measures have been put in place. The Nigerian government implemented bans on international travel from all countries, especially high-risk countries. However, the existence of porous borders limited success, which could have been obtained from the travel ban.Conclusion: COVID-19 mitigation measures should be implemented and reinforced as required nationwide and get provided the needed support. References• World Health Organization. COVID-19 public health emergency of international concern (PHEIC) global research and innovation forum, 2020 February 12. In: WHO 2020. Available from: https://www.who.int/publications/m/item/covid-19-public-health-emergency-of-international-concern-(pheic)-global-research-and-innovation-forum [Accessed on 26 August 2020].]• European centre for disease prevention and control. COVID-19 situation updates worldwide, as of 26 August 2020. In: ECDC 2020. Available from: https://www.ecdc.europa.eu/en/geographical-distribution-2019-ncov-cases [ Accessed on 26 August 2020].]• Nigeria centre for disease control. COVID-19 outbreak in Nigeria situation report. Abuja. In: NCDC. 2020 Contract No.: S/N: 001. Available from: https://covid19.ncdc.gov.ng/ [Accessed on 26 August 2020].• Ogundele K. UPDATED: FG places travel ban on China, Italy, US, UK, nine others. Punch Newspapers, 2020 Mar 18. Available from: https://punchng.com/breaking-fg-places-travel-ban-on-china-italy-us-uk-others/ [ Accessed on 26 August 2020]• Presidential task force on COVID-19. Available from: https://statehouse.gov.ng/covid19/ [Accessed on 26 August 2020].• Okunola A. 5 Challenges facing health care workers in Nigeria as they tackle COVID-19. On 9 June 2020. In: Global citizen. Available from: https://www.globalcitizen.org/en/content/challenges-for-health-care-workers-nigeria-covid/ [Accessed on 26 August 2020].• Sessou E. COVID-19: Why we provided testing kits in Kano- ADF. 2020 May 8. In: Vanguard. Available from: https://www.vanguardngr.com/2020/05/covid-19-why-we-provided-testing-kits-in-kano-adf/ [Accessed on 26 August 2020].• Ilesanmi OS, Afolabi AA. Time to move from vertical to horizontal approach in our COVID-19 response in Nigeria. SciMed J. 2020; 2:28-29. https://doi.org/10.28991/SciMedJ-2020-02-S1-3.• Olisa C. Covid-19: FG orders immediate shut down of all schools. 2020 March 20. In: Naira Metrics [Internet]. Available at: https://nairametrics.com/2020/03/20/covid-19-fg-orders-immediate-shut-down-of-all-schools/ [Accessed on 26 August 2020].• Adejayan G. COVID-19: Lagos decontaminates schools for partial resumption. On 1 August 2020 [cited 26 August 2020]. In: Within Nigeria. Available from: https://www.withinnigeria.com/2020/08/01/covid-19-lagos-decontaminates-public-schools-for-partial-resumption/ [Accessed on 26 August 2020].• Oyetimi K, Adewakun A. E-learning: How COVID-19 is reshaping education in Nigeria. On 10 April 2020. Publish In: MSN. Available at: https://www.msn.com/en-za/news/other/e-learning-how-covid-19-is-reshaping-education-in-nigeria/ar-BB12pMEd [Accessed on 26 August 2020].• Hale T, Webster S, Petherick A, Phillips T, Kira B. Oxford COVID-19 Government Response Tracker, Blavatnik School of Government. 2020 March 21. In: Our World in Data. Oxford COVID-19 government response tracker. Available from: https://ourworldindata.org/grapher/public-gathering-rules-covid?year=2020-08-26&time=2020-01-01.2020-08-04&region=Africa [Accessed on 26 August 2020].• Lagos police command enforces ban on social gatherings to prevent spread of coronavirus. On 22 March 2020. In Vanguard. Available from: https://www.vanguardngr.com/2020/03/lagos-police-command-enforces-ban-on-social-gatherings-to-prevent-spread-of-coronavirus/ [Accessed on 26 August 2020].• Donohue JM, Miller E. COVID-19 and School Closures. JAMA. 2020;324(9):845-847. https://doi.org/10.1001/jama.2020.13092• Sahara Reporters. Nigerian government lifts ban on religious gatherings, reduces curfew hours. On 1 June 2020. In: Sahara Reporters. Available from: http://saharareporters.com/2020/06/01/nigerian-government-lifts-ban-religious-gatherings-reduces-curfew-hours [Accessed on 26 August 2020].• COVID-19: Lagos reels out guidelines for reopening of Mosques, Churches. On 6 August 2020. In: Vanguard. Available from: https://www.vanguardngr.com/2020/08/covid-19-lagos-reels-out-guidelines-for-reopening-of-mosques-churches/ [Accessed on 26 August 2020].• Vanguard. Porous borders, cause of rise in COVID-19 cases — FG. On 3 April 2020. In: Vanguard [internet]. Available from: https://www.vanguardngr.com/2020/04/porous-borders-cause-of-rise-in-covid-19-cases-fg/ [Accessed on 26 August 2020].
Keywords: Coronavirus Disease, COVID-19 Mitigation, Lockdown, Response, Nigeria